2021
DOI: 10.1039/d0cp05890d
|View full text |Cite
|
Sign up to set email alerts
|

Ideal strength and strain engineering of the Rashba effect in two-dimensional BiTeBr

Abstract: Achieving large and tunable Rashba effect is of great significance for advancing both the understanding and applications of spintronics. Two-dimensional nanostructures that are expected to sustain large mechanical deformation provide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Our results indicate that the states near the valence band maximum (VBM) are mainly composed of X -p and Y -p orbitals. In contrast, the conduction band minimum (CBM) states are dominated by the Bi-p orbital in all structures which is in good agreement with the previous studies on BiTeX crystals [61,62]. It is noticed that the spin-orbit splitting in energy bands is more significant in the structures with heavier elements and more distinct broken inversion symmetry.…”
Section: E Electronic Propertiessupporting
confidence: 91%
“…Our results indicate that the states near the valence band maximum (VBM) are mainly composed of X -p and Y -p orbitals. In contrast, the conduction band minimum (CBM) states are dominated by the Bi-p orbital in all structures which is in good agreement with the previous studies on BiTeX crystals [61,62]. It is noticed that the spin-orbit splitting in energy bands is more significant in the structures with heavier elements and more distinct broken inversion symmetry.…”
Section: E Electronic Propertiessupporting
confidence: 91%
“…Due to the geometry-dependent prominence of the Rashba effect, multiple avenues have been explored to tune its strength and effect on band edges, such as the application of electric fields, strain, pressure, and temperature modulation. For example, Ju et al noted the tunability of Rashba spin splitting under electric fields and strain, where N III X VI systems exhibited tunable bandgaps insofar as the centrosymmetry of the lattice was broken . Similarly, using pressure modulation to vary the strength of the Rashba effect, Wang et al demonstrated an increase in the strength of direct transitions in an indirectly gapped perovskite system, which resulted in favorable performance for light absorption .…”
Section: Introductionmentioning
confidence: 99%
“…The tensile strain leads to an increase in the energy for a bonding state and a reduction in the energy for an anti-bonding state. 49 We can first focus on the strain-free ZnSb monolayer and plot the partial charge densities for one conduction band state labeled as C 1 in Fig. 3(e) and two valence band states labeled as V 1 , V 2 in Fig.…”
Section: Resultsmentioning
confidence: 99%